2007
DOI: 10.1590/s0034-72992007000500004
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da acupuntura sobre as emissões otoacústicas de pacientes com zumbido

Abstract: The treatment of tinnitus is still a challenge. Acupuncture is recommended for the relief of tinnitus in traditional Chinese Medicine, although scientific evidence is lacking. Aim: The aim of this study was to assess the effect of acupuncture on the cochlear function in patients with tinnitus by analyzing otoacoustic emissions. Methods: Thirty eight patients with tinnitus were included in the prospective clinical study. Measures of transitory otoacoustic emissions and suppression of otoacoustic emissions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
(33 reference statements)
0
5
0
1
Order By: Relevance
“…Studies have shown that stimulation performed with needles promotes introduction of an electrical charge that triggers action potentials in order to rebalance the system. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that stimulation performed with needles promotes introduction of an electrical charge that triggers action potentials in order to rebalance the system. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…According to Azevedo et al, 35 the auditory perception of tinnitus might be related to dysfunction of the efferent auditory pathway, which would result in the loss of OHC modulation, causing abnormal activity of the auditory pathways that could be wrongly interpreted as sound.…”
Section: Discussionmentioning
confidence: 99%
“…Azevedo et al investigated the effect of acupuncture on OAEs in tinnitus patients and found an increase in the amplitude and suppression of OAEs after acupuncture treatment, 35 suggesting that this method exerts an effect on cochlear function. Lower suppression values were also observed in children with impaired central auditory processing when compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still a lack in scientific literature of evidence to support the therapeutic efficacy of acupuncture. Studies have shown that needle stimulation creates an electric charge that has the potential of triggering a rebalancing of the system [14]. Chinese scalp acupuncture is a contemporary acupuncture technique that has been around for just 40 years.…”
Section: Acupuncturementioning
confidence: 99%